PLANNING ANALYSIS OF SHEET PILE WHARF WITH PLAXIS SOFTWARE AT SPECIAL TERMINAL LAMPUNG - Junetha Syella Tandian; Suwandi Saputro (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2023)
Special terminals are those that are located outside the Working Environment Area and the Interest Environment of the main business. Private companies with business licenses in Lampung Province want the construction of a special port or terminal. The efforts made are to analyze the planning of a special terminal wharf to serve the loading of commodity materials in the form of cement factory materials. A steel sheet pile is used as a structure on the Lampung Wharf. The purpose of this study is to determine the stability and optimality in the selection of sheet pile dimensions used by adjusting the soil conditions around the wharf. The analysis and modeling method using calculations of the Plaxis 8.2 software assistance will get the results of the analysis in the form of safety factor numbers and deformations. From the calculation and modeling of the Plaxis 8.2 software, the results of the deformation analysis are 1,29 mm and a safety factor of 1,7011. It can be concluded that the sheet pile and the selection of sheet pile dimensions used are considered safe. Keywords: port, wharf, sheet pile, Plaxis